2023
DOI: 10.1073/pnas.2216532120
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical HPV carcinogenesis drives radiosensitization of head and neck tumors

Abstract: We analyzed transcriptional data from 104 HPV+ (Human papillomavirus) HNSCC (head and neck squamous cell carcinoma) tumors together with two publicly available sources to identify highly robust transcriptional programs (modules) which could be detected consistently despite heterogeneous sequencing and quantification methodologies. Among 22 modules identified, we found a single module that naturally subclassifies HPV+ HNSCC tumors based on a bimodal pattern of gene expression, clusters all atypical features of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…The association of HPV integration with outcome in head and neck tumors has had varied and conflicting results, with some studies showing no correlation with survival [ 54 , 62 ], some a positive correlation with viral integration [ 56 , 63 ], and others an unfavorable correlation [ 55 , 64 ]. Interestingly, to our knowledge, all studies using transcriptional (e.g., RNAseq) methods to ascertain integration status have found integration to be associated with poor prognosis [ 55 , 64 , 65 ]. A recent multiomics study of uterine cervical cancer categorized integration sites as productive or silent based on the presence or absence of viral-human fusion transcripts [ 66 ].…”
Section: Hpv Carcinogenesis and Prognostic Biomarkers To Guide Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…The association of HPV integration with outcome in head and neck tumors has had varied and conflicting results, with some studies showing no correlation with survival [ 54 , 62 ], some a positive correlation with viral integration [ 56 , 63 ], and others an unfavorable correlation [ 55 , 64 ]. Interestingly, to our knowledge, all studies using transcriptional (e.g., RNAseq) methods to ascertain integration status have found integration to be associated with poor prognosis [ 55 , 64 , 65 ]. A recent multiomics study of uterine cervical cancer categorized integration sites as productive or silent based on the presence or absence of viral-human fusion transcripts [ 66 ].…”
Section: Hpv Carcinogenesis and Prognostic Biomarkers To Guide Therapymentioning
confidence: 99%
“…Testing the profile on four independent cohorts revealed that patients whose tumors had high expression of profile genes had significantly improved survival compared to those with low expression of these genes ( Table 1 ). Tumors assigned to the high expression vs. low expression subtypes were also distinguished by differences in somatic gene alterations, mutational signatures, HPV gene expression, HPV genome integration, and genomic methylation profiles [ 65 ]. The gene profile that identified the two subtypes of HPV+ HNSCC was based on high or low NF-κB signaling and fully recapitulated previous subtypes that our group defined based on the presence or absence of inactivating defects in TRAF3 or CYLD or associated gene expression changes [ 64 , 65 , 73 ].…”
Section: Hpv Carcinogenesis and Prognostic Biomarkers To Guide Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…In a study published in the Proceedings of the National Academy of Sciences, researchers used data from 104 HPV-related head and neck cancer tumors and other sources to identify gene expression patterns (or modules) from which different tumor types could be classified. 1 They found one module (of 22 identified) that was able to effectively categorize HPV-related head and neck tumors on the basis of a distinct gene expression pattern in which tumors were separated into high and low expression. Analysis of this module showed that the genes represented targets of a master transcription factor called nuclear factor-κB (NF-κB), a molecular pathway linked to cellular growth, formation of new blood vessels, and increased protection against cell death.…”
mentioning
confidence: 99%